Dispositional optimism and pessimism in association with cognitive abilities in early and middle adulthood - Karhu, J. (Jutta); Hintsanen, M. (Mirka); Ek, E. (Ellen); Koskela, J. (Jari); Veijola, J. (Juha) (Elsevier, 2022)
Abstract The aim of the current study was to examine the associations of dispositional optimism and pessimism with cognitive abilities in adulthood. We performed two studies with data sets from the prospective Northern Finland Birth Cohort Studies: 26-year-olds (N = 383) and 46-year-olds (N = 5042). In both samples, dispositional optimism and pessimism were measured with Carver and Scheier’s Life Orientation Test -Revised. In the data of 26-year-olds, the cognitive abilities assessed were reasoning, vocabulary, verbal fluency, fine-motor skills, selective attention, impulse control, and memory, while in 46-year-olds, memory was assessed. The analyses were carried out using multiple linear regression, and the associations were adjusted for gender, educational level, mother’s educational level, and depression. Our results indicated that (I.) higher dispositional optimism and lower pessimism were associated with higher reasoning skills in young adults, and (II.) higher pessimism was related to lower scores on memory test in middle-aged adults. The findings provide a closer look on how dispositional optimism and pessimism are associated with the core cognitive abilities in adults.